2012
DOI: 10.1186/1746-4358-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Reasons given by mothers for discontinuing breastfeeding in Iran

Abstract: BackgroundWe have previously shown that in Iran, only 28% of infants were exclusively breastfed at six months, despite a high prevalence of breastfeeding at two years of age. The primary aim of this study was to investigate the reasons women discontinued exclusive breastfeeding.MethodThis retrospective study was based on questionnaires and interviews with 63,071 mothers of infants up to 24 months of age, divided into two populations: infants younger than six months and six months or older. The data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 18 publications
8
60
2
5
Order By: Relevance
“…We did not study the causes of the high rates of non-exclusive breastfeeding, but other studies demonstrate this is due to cultural beliefs, insufficient breast milk production, and maternal illness. 13,14 One potential cause may be difficulty in breast milk production as reported by nearly a quarter of the mothers. Another potential etiology may be given that Daman is a farming community, newly delivered mothers often returned to their field work as was observed, but this data was not exclusively collected.…”
Section: Discussionmentioning
confidence: 99%
“…We did not study the causes of the high rates of non-exclusive breastfeeding, but other studies demonstrate this is due to cultural beliefs, insufficient breast milk production, and maternal illness. 13,14 One potential cause may be difficulty in breast milk production as reported by nearly a quarter of the mothers. Another potential etiology may be given that Daman is a farming community, newly delivered mothers often returned to their field work as was observed, but this data was not exclusively collected.…”
Section: Discussionmentioning
confidence: 99%
“…Bennis et al et al reported that mothers' concerns about milk supply were often identified as an important reason for their decision to stop breastfeeding during the first six months [31]. Such finding was also evoked by Gatti, indicating that the perception of inadequate milk supply is put forth by mothers as the main reason for breastfeeding discontinuation during the first four weeks after delivery and also the most common reason for early cessation [32] and total cessation of breastfeeding [33]. As far as sucking difficulty is concerned, it has been reported that cracked nipples are one of the four variables assessed and associated with an early discontinuation of EB [34].…”
Section: Discussionmentioning
confidence: 71%
“…From the researches done abroad, (with accessible full texts), eight studies, including a meta-analysis, reported a deleterious effect of pacifiers on breastfeeding (17)(18)(19)(20)(21)(22)(23)30); five papers refuted these observations (25,(33)(34)(35)37) and findings from four surveys were inconclusive (24,31,32,36). All three studies from Iran claimed that pacifier use is associated with decreased duration of EBF/predominant breast feeding and early introduction of the bottle (5,19,27).…”
Section: Resultsmentioning
confidence: 99%